Drug Combination in Cancer Treatment—From Cocktails to Conjugated Combinations - Gilad, Yosi (Cancers (Basel), 2021)
SIMPLE SUMMARY: Chemotherapy is a key modality in today’s practice of clinical oncology. The potential for systemic treatment of cancer patients with cytotoxic agents was discovered in the mid 20th century and its major shortcomings namely, off target toxicity and resistance to treatment, were apparent from the very beginning. These limitations pushed the scientific and medical communities to search for improvements, which as a final result, shaping modern research and clinical practice in the field. For minimizing off target toxic effects, drug discovery efforts became more focused on targeted therapies and on combinations of anti-cancer drugs in order to overcome the resistance problem. Here we outline the evolution of chemotherapy from its beginning as a single-agent based therapy to poly-drug treatment that involves targeted drugs, and discuss the concept of drug-conjugation based treatment as a strategy for further optimization of treatment regimes. ABSTRACT: It is well recognized today that anticancer drugs often are most effective when used in combination. However, the establishment of chemotherapy as key modality in clinical oncology began with sporadic discoveries of chemicals that showed antiproliferative properties and which as a first attempt were used as single agents. In this review we describe the development of chemotherapy from its origins as a single drug treatment with cytotoxic agents to polydrug therapy that includes targeted drugs. We discuss the limitations of the first chemotherapeutic drugs as a motivation for the establishment of combined drug treatment as standard practice in spite of concerns about frequent severe, dose limiting toxicities. Next, we introduce the development of targeted treatment as a concept for advancement within the broader field of small-molecule drug combination therapy in cancer and its accelerating progress that was boosted by recent scientific and technological progresses. Finally, we describe an alternative strategy of drug combinations using drug-conjugates for selective delivery of cytotoxic drugs to tumor cells that potentiates future improvement of drug combinations in cancer treatment. Overall, in this review we outline the development of chemotherapy from a pharmacological perspective, from its early stages to modern concepts of using targeted therapies for combinational treatment.